2015
DOI: 10.1017/s0007114515002615
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, retirement and changes in vegetable consumption in France: findings from the prospective GAZEL cohort

Abstract: The aim of this study was to describe the change in vegetable consumption with ageing and the transition to retirement. Study subjects were the participants of the GAZEL prospective cohort (Gaz and Électricité de France) aged 40-49 years at inclusion in 1989 who retired between 1991 and 2008 (12 942 men and 2739 women). Four FFQ were completed from 1990 to 2009. We used multiple imputation by chained equations in order to avoid dropping incomplete cases. The OR for eating vegetables everyday was estimated as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
(87 reference statements)
1
23
0
8
Order By: Relevance
“…A French prospective study found that transition to retirement was associated with a decrease in fruit consumption and overall unhealthier dietary intakes (27) . Other studies have found positive changes, such as an increased consumption of vegetables after retirement in a French prospective cohort study (28) . Some studies have found mixed or no association, including decreased fruit consumption and increased vegetable consumption after retirement in a Dutch longitudinal study among men (29) , and no associations of retirement with fruit and vegetable consumption in a large Australian follow-up study (30) and with fish consumption in the British Whitehall II Study (31) .…”
Section: Discussionmentioning
confidence: 85%
“…A French prospective study found that transition to retirement was associated with a decrease in fruit consumption and overall unhealthier dietary intakes (27) . Other studies have found positive changes, such as an increased consumption of vegetables after retirement in a French prospective cohort study (28) . Some studies have found mixed or no association, including decreased fruit consumption and increased vegetable consumption after retirement in a Dutch longitudinal study among men (29) , and no associations of retirement with fruit and vegetable consumption in a large Australian follow-up study (30) and with fish consumption in the British Whitehall II Study (31) .…”
Section: Discussionmentioning
confidence: 85%
“…Our findings most likely reflect the relatively young age of our older adults. Associations between vegetable consumption and affluence or socio-economic status have also previously been suggested [ 31 , 33 , 56 , 57 , 58 ], and associations between socio-economic status and healthy dietary and lifestyle habits are well known [ 28 , 31 , 50 , 53 , 56 , 58 ]. These associations have largely been associated with the monetary and practical costs of healthy dietary habits, and perceptions of fruits and vegetables as poor-value foods (in terms of energy provided per unit cost or unit effort) are reported [ 49 , 50 , 74 ].…”
Section: Discussionmentioning
confidence: 90%
“…Higher consumption was found in the UK compared to France compared to Italy, but whether these effects are due to the country or due to the different samples studied in each country is unknown. Previous studies and consumption databases typically report a higher vegetable consumption in Southern as opposed to Northern European countries [ 25 , 33 , 57 , 58 , 60 , 73 ], and differences were found between the different samples for each country on several demographic variables, although genuine effects as a result of income/affluence from South to North have also been suggested [ 31 ]. Given the differences between samples, while the analyses within countries are likely to be accurate [ 47 , 67 , 68 , 69 , 70 ], direct comparisons between countries should only be conducted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…may also explain such equivocal results. Two prospective studies showed a positive impact of retirement on dietary intake: higher adherence to several Nordic recommendations were observed in women who retired compared with continuously employed women, and increase of vegetables after retirement in men was reported in another study [13, 14]. However, results on food groups’ consumption are equivocal [15–17].…”
Section: Introductionmentioning
confidence: 99%